Graphene incorporated zinc oxide hybrid nanofluid for energy-efficient heat transfer application: A thermal lens study - Vijayakumar Gokul; Mohanachandran Nair Sindhu Swapna; Sankaranarayana Iyer Sankararaman (Next Nanotechnology)
The work focuses on the development of a hybrid nanofluid (NF) comprising zinc oxide-graphene (ZG) to address heat transfer (HT) limitations in thermal systems. The study employs a highly sensitive mode-mismatched dual-beam thermal lens (MDTL) method to analyze the lattice dislocation-induced thermal diffusivity (D) modifications of the hybrid NF. The hybrid composite (HC) is synthesized by solid-state mixing and annealing of ZG. The formation of ZG hybrid composites is revealed through X-ray diffraction (XRD), Fourier transform infrared, X-ray photoelectron, and Raman spectroscopic analyses. The structural dislocations present in the HC are understood from XRD and Raman analyses. Ultraviolet-visible and photoluminescence spectroscopic studies revealed the optical properties of the samples. The MDTL study is carried out by preparing the NFs of the synthesized samples in the base fluid, ethylene glycol (EG), and reveals the impact of crystallite defects on the thermal characteristics of the synthesized composites. Thus, the study suggests the potential capability of ZG composites in tuning the thermal behaviour of EG for HT applications.